Work-family interfaces and leaders’ knowledge hiding: underlying mechanisms and contingencies - Min, Min; Fang, Kai; Zhang, Zhen; Xu, Ziyue (Frontiers in Psychology, 2025)
ObjectivesThe current study aims to examine the effects of work interference with family (WIF) and family interference with work (FIW) on leaders’ knowledge hiding, as well as the mediating role of affective organizational commitment and the contingent role of organization-based self-esteem.MethodsData were collected through a three-wave survey from 137 new product team leaders in China, with a 2-week interval between waves to reduce common method bias.ResultsOur findings indicate that FIW was positively related to knowledge hiding. This positive linkage was partially mediated by affective organizational commitment. Organization-based self-esteem weakens the impact of FIW on affective organizational commitment. In addition, as affective organizational commitment increased, the positive indirect effect of FIW on knowledge hiding becomes weaker. By contrast, the relevant results related to the effect of WIF were not significant.ConclusionExtant research on micro-innovation has mainly highlighted the within-domain stressful effects of job conflicts but largely neglected their cross-domain mechanisms in shaping leaders’ knowledge behaviors. This study is one of the first to investigate how and when work-family interfaces influence top-down knowledge-hiding behavior. Practically, the findings provide guidance for organizations to design family-supportive and esteem-enhancing HR practices to reduce leaders’ knowledge hiding driven by FIW.